Caracterização ontogenética e agro-fisiológica de cultivares modernas de trigo (Triticum aestivum L.) - Bozi, Antonio Henrique (2017)
Knowing the processes responsible for high yields of grains in different genotypes available in the market is an essential step for the selection of more productive genotypes. The objectives of this study were: a) to evaluate the duration of subperiods of different modern wheat cultivars and to quantify the importance of each subperiod in grain yield and its components b) to characterize physiologically an agronomically modern wheat cultivars in order to identify characters physiological and agronomic characteristics that have a direct correlation with grain yield and its components. Fourteen modern wheat cultivars were evaluated. The experimental design was a randomized complete block design with three replications. The plots were constituted of six lines of 5.0m in length, with spacing between rows of 0.20m, making an area of 6.0sqm. The durations of the subperiods were evaluated: sowing - emergence (SM-EM); emergency - double ring (EM-DA); double ring - terminal spike (DA-ET); terminal spikelet - anthesis (ET-ANT); before - physiological maturation (ANT-MF); sowing - anthesis (SM-ANT) and sowing - physiological maturation (SMMF). And also the characters yield of grains, mass of a thousand grains, number of grains, plant height, harvest index, biological yield, relative content of chlorophyll and gas exchanges for the different modern cultivars. Data were submitted to analysis of variance, and means were compared by the Tukey test (p = 0.005). In addition, the Pearson correlation and the canonical correlation analysis were performed between the groups of characters. The genotypes had the terminal spikelet subperiod with the highest duration (307.19 degrees day), contributing with the increment of the grain yield (r = 0.88), dry ear weight in anthesis (r = 0.81), number of spikelets per spike (r = 0.80) and number of grains per spikelet (r = 0.88). Grain yield was also associated with an increase in the harvest index (r = 0.77), biological yield (r = 0.70), number of grains per spike (r = 0.69) and number of grains per spikelet (r = 0.73). Pretreatment chlorophyll content, stomatal conductance and photosynthetic rate in pre and post before were positively associated with increased grain yield. These results suggest that manipulation of the terminal spikelet subperiod at anthesis, increase of harvest index, yield and number of grains, together with elevation of photosynthetic potential and stomatal conductance in pre and post anthesis may be strategies to be used for the increase of grain yield potential in wheat in breeding programs.